Diagnostic Values of Free Triiodothyronine and Free Thyroxine and the Ratio of Free Triiodothyronine to Free Thyroxine in Thyrotoxicosis - Xinxin Chen; Yulin Zhou; Mengxi Zhou; Qinglei Yin; Shu Wang (International Journal of Endocrinology)
Background. The results of previous studies on the usefulness of free triiodothyronine (FT3) to free thyroxine (FT4) are controversial. We investigated the usefulness of FT3, FT4, and FT3/FT4 ratio in differentiating Graves’ disease (GD) from destructive thyroiditis. Methods. A total of 126 patients with untreated GD, 36 with painless thyroiditis, 18 with painful subacute thyroiditis, and 63 healthy controls, were recruited. The levels of FT3 and FT4 and the FT3/FT4 ratios for the different etiologies of thyrotoxicosis were evaluated separately by receiver operating characteristic (ROC) curve analysis. The expression levels of type 1 and type 2 deiodinase (DIO1 and DIO2) in thyroid tissues were also investigated. Results. The optimal cut-off values were 7.215 pmol/L for FT3, 21.71 pmol/L for FT4, and 0.4056 for the FT3/FT4 ratio. The specificity and positive predictive value of the FT3/FT4 ratio were highest for values > 0.4056. DIO1 mRNA expression was significantly higher in the thyroid tissue of patients with GD (P=0.013). Conclusions. We demonstrated that the FT3/FT4 ratio was useful in differentiating GD from destructive thyroiditis. In addition, a relatively high expression of type 1 deiodinase in the thyroid might be responsible for the high FT3/FT4 ratio in patients with GD.